WORD PROCESSING. - Horning, Rob (Art in America, 2022)
The article looks into a troubling analogue in artificial intelligence (AI) text generators in the Surrealist method of automatic writing, that is text production estranged from human consciousness. Topics discussed are limitations of text outputs of generative models, capacity of AI systems to exhaust imaginative possibility and work through ideas, and business models for the Surrealism-AI symbiosis like generative pre-trained transformer 3 (GPT-3) and generative art non-fungible tokens (NFT).